Diderot et Maupertuis sur la sensibilité de la matière, ou comment feindre de ne pas se comprendre - Soubbotnik, Michael A. (Studia Romanica Posnaniensia, 2020)
In §§ 50-51 of his Pensées sur l’interprétation de la Nature, Diderot draws consequences adverse to religion from the hypothesis of the sensibility of living matter in the Système de la Nature, prompting an endangered Maupertuis to respond. Diderot knows that he is reading his own materialistic conception of matter in Maupertuis but is feigning to object to it, while Maupertuis, who knows that the so-called objection is in truth Diderot’s own view, is compelled to defend himself. Through this rhetoric of feigned misunderstanding, real and fundamental questions (living matter, continuity, totality, unity of natural philosophy) raised by the phenomena of organization are being discussed.